Diagnostic and safety value of ultrasound-guided transthoracic core needle biopsy for mediastinal masses: a single-center experience - Poisa, Paolo; Malerba, Paolo; Orsini, Anna; Sabbadini, Linda; De Tavonatti, Maria Grazia; Cecchinel, Stefania; Orizio, Paola; Caletti, Stefano; Saifi, Erkin Saeed; Nardin, Matteo; Pelizzari, Giovanni (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
US-guided (Ultrasound-guided) percutaneous transthoracic core needle biopsy (CNB) is a favorable method for establishing the correct diagnosis of mediastinal masses. However, studies in this area are scant and often include small samples, thus making it difficult to provide robust evidence regarding the safety and efficacy of this procedure. Thus, we aimed to report on the 20 years of experience at our center with regard to US-guided CNB.We included all consecutive patients referred to our center to undergo US-guided percutaneous transthoracic CNB for a mediastinal mass between 1999 and 2022. Descriptive statistics were used to display data. A multivariate logistic regression analysis was used to inquire about predictors of diagnostic sampling.The final cohort included 140 patients with a median age of 37 years. In 20.7% of the cases, the mediastinal mass was an incidental finding. The parasternal approach was used most often. US-guided CNB was diagnostic in 84.3% of the patients and most of the diagnoses included hematological neoplasms. The reasons for non-diagnostic sampling included firm lesion consistency, low quantity of samples, and lesion necrosis. The parasternal approach resulted in an independent predictor of diagnostic sampling (AOR 4.16, 95% CI 1.14–15.23, p=0.031), while a bulky feature revealed only a trend for diagnostic sampling. One non-severe adverse event occurred, with spontaneous resolution.US-guided percutaneous transthoracic CNB is an effective and safe procedure that allows the diagnosis of mediastinal masses. The identification of patients that could benefit from this technique should be the next step in researching this topic.
Keywords: ultrasound-guided biopsy; core needle biopsy; contrast-enhanced ultrasound; mediastinum